2019
DOI: 10.3389/fnhum.2019.00342
|View full text |Cite
|
Sign up to set email alerts
|

Technological Competence Is a Pre-condition for Effective Implementation of Virtual Reality Head Mounted Displays in Human Neuroscience: A Technological Review and Meta-Analysis

Abstract: Immersive virtual reality (VR) emerges as a promising research and clinical tool. However, several studies suggest that VR induced adverse symptoms and effects (VRISE) may undermine the health and safety standards, and the reliability of the scientific results. In the current literature review, the technical reasons for the adverse symptomatology are investigated to provide suggestions and technological knowledge for the implementation of VR head-mounted display (HMD) systems in cognitive neuroscience. The tec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
196
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(202 citation statements)
references
References 95 publications
(129 reference statements)
3
196
1
2
Order By: Relevance
“…Our findings show that content significantly influences VR sickness symptoms. Recent HMD technology can provide a better experience (Kourtesis et al, 2019) and if this is combined with careful selection of content the risk of VR sickness can be reduced and those symptoms that do occur can be easily managed. In this review, we compared our total SSQ scores with the cut-off scores suggested by Kennedy et al (2003), what these scores mean in relation to HMDs and how these scores relate to the general population remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings show that content significantly influences VR sickness symptoms. Recent HMD technology can provide a better experience (Kourtesis et al, 2019) and if this is combined with careful selection of content the risk of VR sickness can be reduced and those symptoms that do occur can be easily managed. In this review, we compared our total SSQ scores with the cut-off scores suggested by Kennedy et al (2003), what these scores mean in relation to HMDs and how these scores relate to the general population remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…HMDs can differ in terms of field of view, use of stereo, resolution, framerate, availability of inter-pupillary distance controls/adjustment, and other technical display factors. Modern HMDs from the last 5 years differ fundamentally from the more limited display technology that was available before these recent advances (Kourtesis et al, 2019), and since 35% of papers included in this analysis used these older HMDs, it is difficult to predict how those findings would predict the occurrence of symptoms with use of currently available HMDs. Moving forward, there is an obvious need for more controlled laboratory research with standard reference VR environments that are adjustable in terms of content, movement, user interaction, etc.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations